An Exploration of the Accounting Profession – The Stream of Mobile Devices - Victoria Stanciu; Mirela Gheorghe (Journal of Accounting and Management Information Systems (JAMIS), 2017)
Facing the digital era challenge, the accounting profession is implied in its renewal process aiming at responding in an adequate manner to the companies' and society's continuous changing requirements. The paper emphasizes the impact of the information technology on the accounting profession and signals the positive impact and also the concerns brought by mobile devices in the accountants' work and training. In this context, the authors performed a survey aiming to understand the accounting students' perception in regard with IT impact over the accounting profession and the usefulness of mobile devices. The study's findings provide important insights on the mobile devices use in the accounting work and how the teaching process can help students acquire IT skills and awareness on the professional use of mobile devices. The paper contributes to the research on the accounting developments in the digital era demonstrating the benefit of new technologies' implementation and integration of the mobile devices. The Romanian as well as the south-eastern European scientific literature are scarce in regard with mobile use in the accounting profession. In this regard the authors' research provide significant insights aiming at motivate and stimulate the mobile devices use in the accounting profession and in the academic and long life accounting training.
Keywords: M41; A2; O33; 650; Accounting profession; information technology; mobile devices; m-learning